Development of a novel poly-pseudorotaxane poly (m-phenylene isophthalamide) membrane with a biomimetic surface for effective oil-in-water emulsion separation. (October 2022) - Guan, Chengdong; Yang, Lijuan; Zhu, Lijun; Xia, Daohong
Abstract: The fabrication of membranes with the advantages of simple operation and high separation efficiency is considered of great importance to meet the separation challenge of the oil-in-water emulsions produced in various types of industries. Along these lines, in this work, a membrane with a biomimetic gracilaria surface was ingenious designed and manufactured by using poly-pseudorotaxane structured poly ( m -phenylene isophthalamide) (PMIA) for attaining high efficiency of the oil-in-water separation. m-Phenylenediamine (MPD) included by γ-cyclodextrin (γ-CD) was also used to participate in the synthesis of PMIA and introduce more hydroxyl groups into the polymer chains. By the implementation of a non-solvent induced phase-inversion (NIPS) method, the superhydrophilic and the underwater superoleophobic γ-CD@PMIA membrane was successfully fabricated. Under the 0.05 MPa cross-flow filtration test, in addition to the high pure water flux (1366.69 L·m −2 ·h −1 ·bar −1 ) of the γ-CD@PMIA membrane, its separation efficiency for soybean oil-in-water emulsion was higher than 98.20 %. Moreover, during the application of the continuous separation process of up to 4 h, the membrane maintained a stable separation capacity for different oily wastewaters, which proved its good anti-pollution performance. Furthermore, the membrane exhibits good stability in harsh environments, which is of great significance for the future development of membranes with excellent chemical stability. Our work paves the way for the design of a novel biomimetic surface-based membrane with efficient oil-in-water emulsion separation properties. Graphical abstract: Unlabelled Image Highlights: Introduction of hydroxyl groups into PMIA by poly-pseudorotaxane modification Construction of γ-CD@PMIA membrane with biomimetic gracilaria surface Effective separation for oil-in-water emulsions and tolerance to harsh environments Direction for oily sewage treatment by novel biomimetic surface designing